The power of school principals’ ethical leadership behavior to predict organizational health - Mustafa Özgenel; Tuğba Aksu (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study aimed to reveal whether the ethical leadership behaviors of school principals have an impact on organizational health. The relational survey model, one of the quantitative research methods, was preferred as the research method. There were 402 teachers working in public schools in different districts on the Anatolian Side of Istanbul voluntarily participated in the universe of the research in the 2019-2020 academic year. According to the research findings, a positive relationship was found between organizational health and ethical leadership. As the ethical leadership behaviors of school principals increase, the organizational health of the school increases positively. Therefore, it can be said that the ethical behaviors preferred by the principals in the management process are important for the high level of organizational health in schools.